Landscape and Settlement in the Vale of York Archaeological investigations at Heslington East, York, 2003-13 - Roskams, Steve (Reports of the Research Committee of the Society of Antiquaries of London, 2020)
The Vale of York, in North Yorkshire, has been used and shaped by communities since the end of the last Ice Age to the modern day. Its earliest, prehistoric features chart the way in which household groups shifted from mobile to more sedentary forms of occupation over time, culminating in the creation of landscape divisions from the end of the Bronze Age, and then recognisable field systems during the Iron Age. Throughout all periods, a variety of activity types on the landscape has been evident in the landscape, taking significantly different forms in different contexts: water management; the creation of boundaries; agricultural production; structural development, from domestic houses to larger monuments; exchange and consumption; and mortuary practices plus other ritual activity. This volume takes a thematic approach to these activities, revealing much about the area's development. Providing a thematic analysis of the excavated evidence from the Heslington East area, this volume combines the results of commercial, student training and local community fieldwork between 2007 and 2013. A concluding chapter discusses temporal change by looking at key points of transition in landscape activity in the area and interpreting one of the largest exposures of prehistoric and Roman activity in the immediate hinterland of Eboracum, a major Roman town in Britain.